Spread of carbapenemase-producing Morganella spp from 2013 to 2021: a comparative genomic study - Bonnin, Rémy A; Creton, Elodie; Perrin, Amandine; Girlich, Delphine; Emeraud, Cecile; Jousset, Agnès B; Duque, Mathilde; Jacquemin, Aymeric; Hopkins, Katie; Bogaerts, Pierre; Glupczynski, Youri; Pfennigwerth, Niels; et al. (The Lancet. Microbe, 2024)
BACKGROUND: Morganella spp are opportunistic pathogens involved in various infections. Intrinsic resistance to multiple antibiotics (including colistin) combined with the emergence of carbapenemase producers reduces the number of active antimicrobials. The aim of this study was to characterise genetic features related to the spread of carbapenem-resistant Morganella spp. METHODS: This comparative genomic study included extensively drug-resistant Morganella spp isolates collected between Jan 1, 2013, and March 1, 2021, by the French National Reference Center (NRC; n=68) and European antimicrobial resistance reference centres in seven European countries (n=104), as well as one isolate from Canada, two reference strains from the Pasteur Institute collection (Paris, France), and two colistin-susceptible isolates from Bicêtre Hospital (Kremlin-Bicêtre, France). The isolates were characterised by whole-genome sequencing, antimicrobial susceptibility testing, and biochemical tests. Complete genomes from GenBank (n=103) were also included for genomic analysis, including phylogeny and determination of core genomes and resistomes. Genetic distance between different species or subspecies was performed using average nucleotide identity (ANI). Intrinsic resistance mechanisms to polymyxins were investigated by combining genetic analysis with mass spectrometry on lipid A. FINDINGS: Distance analysis by ANI of 275 isolates identified three groups: Morganella psychrotolerans, Morganella morganii subspecies sibonii, and M morganii subspecies morganii, and a core genome maximum likelihood phylogenetic tree showed that the M morganii isolates can be separated into four subpopulations. On the basis of these findings and of phenotypic divergences between isolates, we propose a modified taxonomy for the Morganella genus including four species, Morganella psychrotolerans, Morganella sibonii, Morganella morganii, and a new species represented by a unique environmental isolate. We propose that M morganii include two subspecies: M morganii subspecies morganii (the most prevalent) and M morganii subspecies intermedius. This modified taxonomy was supported by a difference in intrinsic resistance to tetracycline and conservation of metabolic pathways such as trehalose assimilation, both only present in M sibonii. Carbapenemase producers were mostly identified among five high-risk clones of M morganii subspecies morganii. The most prevalent carbapenemase corresponded to NDM-1, followed by KPC-2, and OXA-48. A cefepime-zidebactam combination was the most potent antimicrobial against the 172 extensively drug-resistant Morganella spp isolates in our collection from different European countries, which includes metallo-β-lactamase producers. Lipid A analysis showed that the intrinsic resistance to colistin was associated with the presence of L-ARA4N on lipid A. INTERPRETATION: This global characterisation of, to our knowledge, the widest collection of extensively drug-resistant Morganella spp highlights the need to clarify the taxonomy and decipher intrinsic resistance mechanisms, and paves the way for further genomic comparisons. FUNDING: None.
Keywords: Whole Genome Sequencing; genom bakteriální; Drug Resistance, Multiple, Bacterial; fylogeneze; Microbial Sensitivity Tests; Europe; Genome, Bacterial; Colistin; mnohočetná bakteriální léková rezistence; lidé; Bacterial Proteins; Humans; mikrobiální testy citlivosti; Evropa; Morganella; Anti-Bacterial Agents; sekvenování celého genomu; beta-laktamasy; kolistin; Genomics; enterobakteriální infekce; Phylogeny; Enterobacteriaceae Infections; beta-Lactamases; karbapenemy; Carbapenems; genomika; antibakteriální látky; bakteriální proteiny